Self-adhesive, self-healing, conductive organogel strain sensors with extreme temperature tolerance. Issue 41 (3rd October 2022) - Dai, Tianyi; Wang, Jing; Wu, Hao; Lin, Yankun; Zhang, Xumin; Ye, Mingyu; Wang, Jingyi; Jia, Hongbing
Abstract : A strain sensor with harsh temperature tolerance, good self-healing ability, self-adhesion, and super elongation at break is constructed based on PEO organogels. Abstract : Conductive hydrogels have highlighted their potential in the fields of electronic skin, soft robotics, and healthcare monitoring, due to their excellent flexibility, tissue-like compliance, and biocompatibility. However, most conductive hydrogels suffer from poor mechanical strength, unsatisfied self-healing properties, and bad temperature tolerance. Herein, we designed a novel ionic organogel based on poly(acrylic acid- co -4-vinylphenylboronic acid) (P(AA- co -VBA)), polyethylene oxide (PEO), tannic acid (TA), and LiCl by simple one-pot radical copolymerization. After elaborately optimizing, the obtained organogel has extremely high mechanical properties (a tensile strength of 0.25 MPa, and an elongation at break of 3200%), good self-healing properties (24 h, 81% self-healing efficiency), and extreme temperature tolerance (from −20 °C to 90 °C). The strain sensor based on the obtained organogel had excellent self-adhesive properties and could closely adhere to the skin to detect temperatures from 0 °C to 42 °C (temperature coefficient of resistance, TCR, at 35 °C is −0.10468 °C −1 ). The strain sensors also monitor large, subtle body movement within a wide temperature range. It is foreseeable that this ionic organogel will provide new inspiration for the development of flexible strain sensors.